Jamaican Mothers’ Perceptions of Children’s Strategies for Resisting Parental Rules and Requests - Burke, Taniesha; Kuczynski, Leon (Frontiers in Psychology, 2018)
Research on Jamaican socialization of children has primarily focused on parental discipline practices. Little is known about children’s responses to parental attempts to control their behavior. The present study investigated mothers’ perceptions of children’s strategies for resisting their rules and requests. Thirty mothers living in Kingston and St. Andrew, Jamaica, participated in a one to one-and-a-half-hour semi-structured, open-ended interview regarding their 8 to 12-year-old children. Mothers reported that their children’s resistance strategies included assertive refusal, arguing, ignoring/avoiding, attitude, and negotiation. Most mothers disapproved of their children’s actions and responded with power-assertive strategies such as physical punishment, psychological control, and forced compliance and threats. Few mothers responded with autonomy support strategies including accommodation and reasoning. The findings provided insight into the ways Jamaican children use their agency to protect their autonomy despite their mothers’ greater power, and the relational nature of children’s influence on their mothers’ behaviors and reactions. More research is needed to expand our knowledge of child agency in Afro-Caribbean families and the various ways that parents may support their growing autonomy that is socially constructive.